Madhya Bharat Roadways Five Year Development Plan 1956-61 - Planning Commission (Planning Commission, 1956)
Though the Government had taken the above policy decision in regard to the Nationalisation of Passenger Road Transport in the State a few years ago, want of adequate finances had always been a stumbling block in its early implementation. Even the Five Year Scheme for Nationalisation through formation of a Road Transport Corporation drawn and submitted to the Government, had to be worked out within a limited finance of TWO CRORES at the cost of many of its -salient features.
Government of Madhya Pradesh